Diagnostics of postnecrotic pancreatic cysts (review of literature) - D. V. Cherdantsev; O. V. Pervova; I. G. Noskov; D. V. Fokin; A. A. Kazadaeva; I. A. Kazadaeva (Вестник хирургии имени И.И. Грекова)
The problem of diagnosing postnecrotic cysts of the pancreas is considered in this article. The characteristics of laboratory (determination of the level of amylase, cytological research of punctate, determination of tumor markers) and radiation (ultrasound, endosonography, RCP, MSCT, etc.) methods of research of this pathology are presented, their specificity in the differential diagnosis of cystic formations, depressurization of the main pancreatic duct and formation of the cyst wall is considered. We concluded that the use of radiation methods of research significantly improves the diagnosis of pseudocyst of the pancreas and allows to choose a rational treatment tactics and an adequate surgical intervention.